Determination of partition coefficients of antiglaucoma drugs between erythrocytes and the medium - Rudenko, S. V.; Saeid, Mohammed Kh. (Biophysical Bulletin, 2009)
In this work, the effect of some antiglaucoma drugs on the shape of human erythrocytes was investigated. It has been shown that increasing drug concentration leads to shape transformation of erythrocytes from discs toward spheres. Using the established dependence of shape index versus drug concentration in the medium the method to measure a free drug concentration based on the implementation of erythrocytes as a biological sensor was developed. This assay was further employed to determine partition coefficients for erythrocytes and pink ghosts which did not vary significantly among different drugs and had an order of 1⋅103. For Benzalkonium chloride, which is a common agent for all drugs an estimate of the number of molecules bound to the red blood cell membrane and an increase in its surface area depending on the shape of the cell has been done.